The Implementation of Dalihan Na Tolu Values as Christian Education in Approaching Domestic Violence Conflict Resolution - Amirrudin Zalukhu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Domestic Violence (DV) remains a significant social issue in Indonesia, causing profound negative effects on individuals, families, and society at large. This study aims to explore how the integration of Dalihan Na Tolu values—an indigenous Batak cultural wisdom—with Christian education can contribute to the peaceful and harmonious resolution of DV conflicts. Dalihan Na Tolu emphasizes principles such as respect for family, gentle treatment of women, and mutual respect within the extended family, which align closely with Christian teachings on love, forgiveness, and reconciliation. The integration of Dalihan Na Tolu values with Christian education offers a holistic approach that combines the strengths of both cultural and religious frameworks in conflict mediation and resolution. Using a qualitative research method based on literature analysis, this study examines the application of values such as love, forgiveness, and reconciliation within the family context. The findings indicate that the combination of indigenous cultural wisdom and Christian education provides an effective and culturally relevant solution to address DV and promote family harmony. Therefore, the roles of the church, cultural leaders, and families are essential for successfully implementing this integrated approach. This research highlights the importance of leveraging both cultural and religious dimensions in developing comprehensive strategies to mitigate domestic violence and foster sustainable family well-being.